Analisis pengaruh struktur aktiva, manajemen hutang, dan manajemen piutang terhadap profitabilitas perusahaan - Firnanti, Julita; Ispriyahadi, Heri; Sembiring, Edison Cholia (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study is to analyze the effect of asset structure, debt management, accounts receivable management on the profitability of tire companies listed on the BEI 2010-2020 and analyze the asset structure, debt management, and receivables management simultaneously on the profitability of tire companies listed on the BEI 2010 -2020. This study uses quantitative research methods because the data obtained in the form of numbers (numeric). The population used in this study are companies engaged in tire companies listed on the Indonesia Stock Exchange (IDX) since 2010-2020, totaling 4 companies. The technique for determining the sample in this research is using a purposive sampling technique. The results of this study are only receivable management (ARTO) which has a significant effect on the profitability of the tire company studied, while asset structure and debt management have no significant effect. Therefore, receivable management is the receivables turnover ratio which is the main variable in increasing the company's profitability.